2013
DOI: 10.1016/j.hrthm.2012.12.015
|View full text |Cite
|
Sign up to set email alerts
|

Sympathetic nerve fibers and ganglia in canine cervical vagus nerves: Localization and quantitation

Abstract: Background Cervical vagal nerve (CVN) stimulation may improve left ventricular ejection fraction in patients with heart failure. Objectives To test the hypothesis that sympathetic structures are present in the CVN and to describe the location and quantitate these sympathetic components of the CVN. Methods We performed immunohistochemical studies of the CVN from 11 normal dogs and simultaneously recorded stellate ganglion nerve activity, left thoracic vagal nerve activity, and subcutaneous electrocardiogram… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
51
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 44 publications
(58 citation statements)
references
References 34 publications
5
51
0
2
Order By: Relevance
“…Similar sympathetic structures have previously been observed in the canine cervical vagus nerve, although the fibres were distributed to the periphery of the nerve (Onkka et al, 2013). This apparent evolutionary vestige is in line with other species where sympathetic and vagus fibres may be transmitted to the thorax via a common trunk (Muryobayashi et al, 1968;Onkka et al, 2013). In addition, anatomical studies have documented rich interactions between the right thoracic vagal nerve and the right stellate ganglion at all levels (Ellison et al, 1969;Mizeres, 1955) and the rat superior cervical ganglia have been found to contain bundles of nerve fibres derived from the vagus nerve that are immunoreactive for calcitonin gene-related peptide and substance P (Zaidi et al, 2013).…”
Section: Tvns and Not Vns?supporting
confidence: 80%
See 1 more Smart Citation
“…Similar sympathetic structures have previously been observed in the canine cervical vagus nerve, although the fibres were distributed to the periphery of the nerve (Onkka et al, 2013). This apparent evolutionary vestige is in line with other species where sympathetic and vagus fibres may be transmitted to the thorax via a common trunk (Muryobayashi et al, 1968;Onkka et al, 2013). In addition, anatomical studies have documented rich interactions between the right thoracic vagal nerve and the right stellate ganglion at all levels (Ellison et al, 1969;Mizeres, 1955) and the rat superior cervical ganglia have been found to contain bundles of nerve fibres derived from the vagus nerve that are immunoreactive for calcitonin gene-related peptide and substance P (Zaidi et al, 2013).…”
Section: Tvns and Not Vns?supporting
confidence: 80%
“…Moreover, Verlinden and colleagues found that the human right cervical vagus contains around twice as many sympathetic fibres as the left cervical vagus (Verlinden et al, 2016). Similar sympathetic structures have previously been observed in the canine cervical vagus nerve, although the fibres were distributed to the periphery of the nerve (Onkka et al, 2013). This apparent evolutionary vestige is in line with other species where sympathetic and vagus fibres may be transmitted to the thorax via a common trunk (Muryobayashi et al, 1968;Onkka et al, 2013).…”
Section: Tvns and Not Vns?supporting
confidence: 57%
“…They have a strong sympathetic output, as demonstrated by Norris et al 20 We observed that the ansae subclaviae directly innervate the vagal trunk, as reported previously. 18,21,22 Sheikh-Zade et al reported that in acute experiments on cats, stimulation of the ansae subclaviae potentiated the effects of vagal stimulation.…”
Section: Effects Of Stepwise Sympathetic Denervationmentioning
confidence: 99%
“…Broadly, parasympathetic and sympathetic inputs are mediated via the vagal nerve and stellate ganglion respectively, although considerable overlap exists. 32 Intrinsic parasympathetic and sympathetic neural inputs are heavily co-localised with up to 30% having dual adrenocholanergic properties -making selective targeting of autonomic activity by localised ablation difficult. By far most intrinsic cardiac nerve complexes are located in the atria, often congregating in known arrhythmogenic 'hot spots' such as the PV/LA junction and have been heavily implicated in arrhythmogenesis.…”
Section: Multi-channel Active Agentsmentioning
confidence: 99%